Implementasi Sistem Manajemen Keselamatan dan Kesehatan Kerja pada Proyek Pembangunan Universitas Terbuka Surabaya - Prasinanda, Evani; Caroline, Jenny (Universitas Batanghari Jambi, 2025)
A construction project is an activity that has a time limit for implementation, activities in construction projects are temporary. Before the project begins, a period for the start and end of the work is usually set. Implementation of a management system that focuses on occupational health and safety (K3) is very necessary in ongoing construction projects. Currently, PT. Tunas Jaya Sanur is building the Open University of Surabaya, which calls for an effective management system for occupational health and safety. This is to make the workplace safe and comfortable for employees and to prevent and lessen the likelihood of work accidents. The research aims to analyze the implementation of K3 and K3 monitoring through questionnaires distributed to management staff, K3 staff, and field workers. The method used in this research is a quantitative method, using survey methods and statistical analysis. The research results show that in the development of the Open University of Surabaya has developed an excellent Occupational Safety and health management system as well as the classification of the level of achievement of respondents (TCR).